2001
DOI: 10.1210/jcem.86.3.7365
|View full text |Cite
|
Sign up to set email alerts
|

What Are the Physical Characteristics Associated with a Normal Metabolic Profile Despite a High Level of Obesity in Postmenopausal Women?1

Abstract: Although obesity is often associated with insulin resistance and a cluster of metabolic disturbances, the existence of a subgroup of healthy but obese individuals has been postulated. It is unclear why some obese individuals fail to show traditional risk factors associated with the insulin resistance syndrome despite having a very high accumulation of body fat. To address this issue, we identified and studied a subgroup of metabolically normal but obese (MNO) postmenopausal women to gain insight into potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
0
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 158 publications
(53 citation statements)
references
References 36 publications
5
36
0
6
Order By: Relevance
“…Thigh muscle size has previously been shown to be negatively associated with mortality risk in both normal weight and overweight elderly populations (66–96 years) [28]. In men, muscle mass, specifically in the lower limbs, was inversely associated with visceral fat [27], but more research on the relationship between LM and metabolic function in women is needed [22,19]. …”
Section: Introductionmentioning
confidence: 99%
“…Thigh muscle size has previously been shown to be negatively associated with mortality risk in both normal weight and overweight elderly populations (66–96 years) [28]. In men, muscle mass, specifically in the lower limbs, was inversely associated with visceral fat [27], but more research on the relationship between LM and metabolic function in women is needed [22,19]. …”
Section: Introductionmentioning
confidence: 99%
“…Although the mechanisms underlying this metabolic profile are not yet clear, it has been suggested that the number of years that an individual has been obese, the person’s metabolic activity, and the distribution and histological characteristics of adipose tissue play a more important role than the amount of adipose tissue in determining metabolic health among obese individuals 48,49. Moreover, studies have reported that individuals with MHO have lower levels of C-reactive protein,50 higher levels of insulin,51 better CRF levels, and better general physical fitness than obese individuals with metabolic syndrome 52. Finally, scientific evidence supports the idea that individuals with MHO have less sedentary behavior time and higher levels of CRF than individuals with metabolically unhealthy obesity 53.…”
Section: Discussionmentioning
confidence: 99%
“…В настоящее время этот феномен известен под названием «metabolically healthy obesity», «метаболически здоровое ожирение» (МЗО) или также его называют «парадокс ожирения», «метаболически здоровое состояние у лиц с ожирением», «неполный метаболический синдром» [3]. Несмотря на наличие избыточного веса или ожирения, у данной когорты пациентов можно наблюдать благоприятный метаболический профиль, характеризующийся сохраненной инсулиночувствительностью, отсутствием АГ, нормальным липидным, гормональным профилем, отсутствием воспаления и неизмененными печеночными ферментами [4][5][6][7]. В настоящее время неизвестны индивидуальные факторы и механизмы, лежащие в основе протективного профиля МЗО.…”
Section: обоснованиеunclassified